Extraction and Analysis of Tectonic Lineaments using Geoinformatic Techniques, in Tawke Oil Field, Duhok area, Iraqi Kurdistan Region - Omar, Abdulla Amir; Ali, Rebar Tahssen (Sulaimani Journal for Pure and Applied Sciences, 2016)
Geoinformatic techniques applied for tectonic lineament extraction and analysis in Tawke Oil field, Kurdistan region of Iraq. Two satellite images have been used, which were Landsat ETM+ and ASTER images to extract lineaments both visually and automatically. It comprises several steps, which involve several enhancing techniques e.g. Color Composite, Spectral Rationing and Principle Component Analysis. From combination of all techniques, the final surface lineaments have been extracted. The final lineament map has been divided in to two maps; local lineament map which was checked in the field and regional lineament map which was confirmed by geophysical data (seismic and gravity data). Local lineaments are evaluated in order to extract further information on the spatial distribution and nature of the lineaments. For this purpose lineament density, length, and lineaments intersection maps are prepared. In addition; the field work was carried out to verify lineaments resulted from satellite images with the observed fractures on the ground through visiting of 17 stations around the Tawke anticline. Orientations of local lineaments (frequency and length) obtained from satellite image were compared with the orientation of fractures (frequency and length) that obtained from the field, using rose diagrams which show a similarities between them, as being concentrated in NE-SW, NW-SE, E-W and N-S, as well as these Lineaments reflect a set and systems of fractures with in studied outcrops. Two types of fractures are recognized one are shear fractures and second are tension fractures. Stereographic projection figured out for confirming the direction of fractures in the field and analyzing the paleostress direction within studied area. Geophysical data (gravity and seismic) have been used for confirming the regional lineaments. Integration has been made between satellite image lineaments and lineaments appeared in geophysical data (gravimetric and seismic lineaments) , there is a coincidence both in the positions, length and azimuths of gravimetric lineaments, seismic lineaments and lineaments appear on satellite image (i.e. surface lineaments). It has been observed that two mechanisms are responsible for giving the architectural shape of study area one is due to block-faulting related to basement faults activity from at least the Middle Paleozoic and continued intermittently up to Late Tertiary, while the second mechanism is due to compressive horizontal stress that have been active since Middle – Late Cretaceous continued up to Late Tertiary.
Keywords: Satelliteimages,Lineaments; seismic,gravity; fractures